Determinan Faktor Likuiditas pada Perusahaan Sub Sektor Otomotif Yang Terdaftar Di Bursa Efek Indonesia - Khairul Anwar Pulungan (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
This study aims to determine the factors that affect liquidity in the automotive sub-sector companies listed on the Indonesia Stock Exchange. The liquidity in this study is measured by using the Current ratio. The research approach uses associative, with a population of 13 companies and taking a sample of 7 companies in the automotive sub-sector. The data analysis technique used is multiple linear regression. Based on the research, it can be concluded that the operating activity cash flow partially has a significant effect on the Current Ratio. Net Profit Margin partially has a significant effect on the Current Ratio. Operating Activities Cash Flow and Net Profit Margin simultaneously have a significant effect on the Current Ratio